Influence of Construction of the following Tunnel on the Preceding Tunnel in the Reinforced Soil Layer - Changfu Huang; Kun Zhou; Bi Deng; Dong Li; Qilong Song; Dong Su (Applied Sciences, 2022)
In coastal cities, some paralleled twin tunnels must be constructed in soft soil layers, and stratum reinforcement is necessary to enhance the stability of the tunnel. However, the influence of construction of the following tunnel on the preceding tunnel in reinforced strata is not clear. This study focuses on four kinds of reinforcement strategies: ring reinforcement of the right tunnel (RR), ring reinforcement of the left tunnel (LR), ring reinforcement of twin tunnels (TR), and cement wall reinforcement between left and right tunnels (CR). The interaction mechanism of the twin tunnels during construction, in terms of surface settlement, tunnel deformation, convergence deformation of the tunnel lining, and internal force of the tunnel lining, is revealed by a series of three-dimensional numerical analyses. It was found that the LR offers an appropriate strategy in terms of both engineering safety and cost savings, and it can significantly reduce the disturbance of the following tunnel excavation on the preceding tunnel.